Kajian Kesesuaian Fungsi Taman Duta Harapan Sebagai Ruang Terbuka Publik Kota Bekasi - Satrio Mukti Wibowo; Nurini Nurini (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Public open space is one of the life supporting elements within certain areas. The existence of public open space in the form of urban parks or other related shapes might be featured with some important function for the surrounding community which acted as a space for activity, recreation, and human interaction. Along with regional development progression, the functional conformity of a park as a public open space may decrease and it might also affect Taman Duta Harapan in Bekasi. This may occur as a consequence of Government's lack of sustainable maintenance in all aspects. Therefore, this study aims to determine the suitability of urban park functions as public open space in Taman Duta Harapan Bekasi by considering local people's perception towards ecological, social, economic, and aesthetic function. Quantitative and qualitative methods with descriptive approach will be applied in this research, given further assistance by the Index of Qualitative Variation (IQV) analysis tool. This research conducts 4 variables in which consists of 17 indicators, hence the results found that there are 10 unqualified items that cannot be used to measure the conformity percentages. Seven qualified indicators are adequate cool air, park shades, flood protections, sports venues, community activities, street vendors, and accessible way to the park. Those seven qualified indicators could be used to measure the compatibility percentage of Taman Duta Harapan functions, and the result stated that the final conformity percentages were counted around 41.1% which means that Taman Duta Harapan has not qualified yet as one of the public open space in Bekasi City.